2013
DOI: 10.3141/2394-02
|View full text |Cite
|
Sign up to set email alerts
|

Toward People's Cities through Land use and Transport Integration

Abstract: Between 2005 and 2012, India's Jawaharlal Nehru National Urban Renewal Mission (JnNURM) invested US$20 billion in urban infrastructure and basic services for the urban poor. The transport program under JnNURM is an important advance, helping cities with policies and funding for moving people, not vehicles. Nevertheless, this program has not sufficiently shifted investment in the urban transport sector from road widening and road expansion to sustainable transport. Urban characteristics and transport needs of I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…As a result, several bus systems confront challenges in planning, implementation, and operation. A review of 13 bus systems in Latin America and Asia (Hidalgo and Carrigan, 2011) indicated that projects brought social, economic, and environmental improvements, but “No project was perfectly executed, due to a combination of institutional, technical, financial and/or politically induced time constraints. Initial implementation was generally rushed, causing operational and user problems. Financial and institutional sustainability was not necessarily assured. Bus Rapid Transit routes were often not fully integrated into the rest of the cities’ public transport system. Many projects faced extensive challenges in accommodating regular city traffic. In cities where BRT services were new, or expanded quickly, public information and user education was poor.” …”
Section: Common Issues With Brtmentioning
confidence: 99%
“…As a result, several bus systems confront challenges in planning, implementation, and operation. A review of 13 bus systems in Latin America and Asia (Hidalgo and Carrigan, 2011) indicated that projects brought social, economic, and environmental improvements, but “No project was perfectly executed, due to a combination of institutional, technical, financial and/or politically induced time constraints. Initial implementation was generally rushed, causing operational and user problems. Financial and institutional sustainability was not necessarily assured. Bus Rapid Transit routes were often not fully integrated into the rest of the cities’ public transport system. Many projects faced extensive challenges in accommodating regular city traffic. In cities where BRT services were new, or expanded quickly, public information and user education was poor.” …”
Section: Common Issues With Brtmentioning
confidence: 99%
“…Despite the difficulties and obstacles, the Indian government has initiated some projects and initiatives aimed at enhancing pedestrian facilities in Indian cities ( 2830 ). The declaration of the National Urban Transport Policy (NUTP) by the Indian government in 2006 was a big step forward ( 28 ); it ensured the provision of facilities for non-motorized transport (NMT) in urban areas ( 31 , 32 ).…”
Section: Literature Surveymentioning
confidence: 99%
“…To give effect to this, the program provided for an outlay of central assistance of more than Rs66,000 crore for the seven-year period, and linked the release of assistance to completion of the reforms. Currently 138 urban transport projects have been approved, with the majority (80 per cent) in Category A cities with populations of at least four million (Hidalgo et al, 2012).…”
Section: C) Jawaharlal Nehru National Urban Renewal Mission (Jnnurm)mentioning
confidence: 99%